THE MENTION OF SHAYKHS IN ALISHER NAVOI'S WORKS - Muftullayeva, Gavhar (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the literary, spiritual, and didactic functions of Sufi shaykhs in Navoi’s works, particularly focusing on Khamsat al-Mutahayyirin, Haloti Sayyid Hasan Ardasher, and Haloti Pahlavon Muhammad. Method: The research examines Alisher Navoi's memoir-biographical texts through a contextual literary analysis, categorizing the representations of Sufi shaykhs into roles such as instructional, educational, and discourse-based, and aligning them with Sufi doctrine. Result: The research demonstrates that Navoi strategically integrates these figures to emphasize the concept of the “Perfect Human,” exemplify spiritual virtues, and underscore the moral alignment of his mentors with Sufi principles. His references vary contextually—from autobiographical reminiscence to symbolic illustration. Novelty: Navoi’s connection to Sufi thought is widely acknowledged, but the nuanced portrayal and purpose of mentioning specific shaykhs across different genres of his writings have not been thoroughly examined. By offering a structured understanding of their representation in Navoi’s narrative, these findings deepen the scholarly interpretation of Navoi’s Sufi worldview and invite further exploration of how literary form and spiritual content are harmonized in Central Asian classical literature.